Fermentation of Chicory Fructo‐Oligosaccharides and Native Inulin by Infant Fecal Microbiota Attenuates Pro‐Inflammatory Responses in Immature Dendritic Cells in an Infant‐Age‐Dependent and Fructan‐Specific Way - Logtenberg, Madelon J. (Mol Nutr Food Res, 2020)
SCOPE: Inulin‐type fructans are commonly applied in infant formula to support development of gut microbiota and immunity. These inulin‐type fructans are considered to be fermented by gut microbiota, but it is unknown how fermentation impacts immune modulating capacity and whether the process of fermentation is dependent on the infant's age. METHODS AND RESULTS: The in vitro fermentation of chicory fructo‐oligosaccharides (FOS) and native inulin are investigated using pooled fecal inocula of two‐ and eight‐week‐old infants. Both inocula primarily utilize the trisaccharides in FOS, while they almost completely utilize native inulin with degree of polymerization (DP) 3–8. Fecal microbiota of eight‐week‐old infants degrades longer chains of native inulin up to DP 16. This correlates with a higher abundance of Bifidobacterium and higher production of acetate and lactate after 26 h of fermentation. Fermented FOS and native inulin attenuate pro‐inflammatory cytokines produced by immature dendritic cells (DCs), but profiles and magnitude of attenuation are stronger with native inulin than with FOS. CONCLUSION: The findings demonstrate that fermentation of FOS and native inulin is dependent on the infant's age and fructan structure. Fermentation enhances attenuating effects of pro‐inflammatory responses in DCs, which depend mainly on microbial metabolites formed during fermentation.